SISTEM PENDUKUNG KEPUTUSAN UNTUK MENENTUKAN LOKASI WISATA YANG TEREKOMENDASI DI KOTA MEDAN DENGAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) BERBASIS WEB - Zulfahmi Indra (Universitas Trilogi, 2023)
Tourism is an activity that is inseparable from human life. Everyone needs to travel and tourism can be done inside and outside the area where they live. The basis of the concept of tourism is people, geographical areas, both origin, and tourist destinations as well as industries that provide tourist facilities and services. The tourist attractions of the city, especially the city of Medan, are very many, but there are very few visitors. To make it easier for prospective tourists to know more tourist attractions with accurate information and recommendations for selecting tourist attractions that match the selected criteria, a computerized system is needed that contains all information on tourist areas online which is expected to be used to obtain information and support for decisions on the selection of tourist attractions effectively. One of the right solutions is to create a decision support system application with the Simple Additive Weighting. In this regard, to create a web-based application to assist tourists in obtaining information, making decisions on the selection of tourist attractions effectively and able to help the community to determine the location of the tourist attraction they are going to. The type of research used in this research is research and development or often known as Research and Development (R & D). A decision support system to determine web-based tourist destinations for the Pariwsiata office of Medan city, to make it easier for the Medan City Tourism Office to promote tourism in the city of Medan.